2022
DOI: 10.3390/ijms23126506
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Molecular Scenarios for Tumorigenic Remodeling of Extracellular Matrix Based on Gene Expression Profiling in Equine Skin Neoplasia Models

Abstract: An important component of tissues is the extracellular matrix (ECM), which not only forms a tissue scaffold, but also provides the environment for numerous biochemical reactions. Its composition is strictly regulated, and any irregularities can result in the development of many diseases, including cancer. Sarcoid is the most common skin cancer in equids. Its formation results from the presence of the genetic material of the bovine papillomavirus (BPV). In addition, it is assumed that sarcoid-dependent oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…We also found that predicted target genes in GO analysis were significantly associated with the extracellular matrix disassembly pathway. As we previously mentioned the changes in ECM composition are reported to play a critical role in the development of horse sarcoids (Martano et al 2016 ; Podstawski et al 2022 ). These results indicated that lncRNAs may play certain roles in the expression of ECM-related genes and play important roles in the pathogenesis of equine sarcoids.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We also found that predicted target genes in GO analysis were significantly associated with the extracellular matrix disassembly pathway. As we previously mentioned the changes in ECM composition are reported to play a critical role in the development of horse sarcoids (Martano et al 2016 ; Podstawski et al 2022 ). These results indicated that lncRNAs may play certain roles in the expression of ECM-related genes and play important roles in the pathogenesis of equine sarcoids.…”
Section: Discussionmentioning
confidence: 84%
“…For example, it was reported that the expression level of lncRNA H19 was significantly downregulated in the metastatic prostate cancer cell line and negatively correlated with the expression of the extracellular matrix protein TGFBI (Zhu et al 2014 ). Previous studies demonstrated that an imbalance of the ECM and an abnormal expression of its genes play a major role in sarcoid pathogenesis (Martano et al 2016 ; Podstawski et al 2022 ). It is therefore of interest, that our study showed upregulation of three lncRNAs — ENSECAG00000046740 , ENSECAG00000058013 , and ENSECAG00000048455 that may be connected with aberrant expression of their correlated genes, and thus indirectly affect the stability of the extracellular matrix during sarcoid formation and progression.…”
Section: Discussionmentioning
confidence: 99%